Correlation of Pseudoelastic NiTi Egineering and True Stress-Strain Curves on the Effects of Nickel Titanium Composition - Abd Hamid, Nubailah; Adnan, Azlan; Hussain Ismail, Muhammad; Ibrahim, Azmi (International Journal of Engineering and Technology, 2019)
This research highlights the novel properties of pseudo-elastic Ni-Ti bar owing to their ability to reverse macroscopicallyÂ inelastic deformation during earthquake known as recentering capability and large elastic strain capacity whichÂ originated from the reversible austenite to martensite phase transformation.Â Hence, this paper presents and evaluatesÂ the cyclicÂ properties of pseudo elastic Niâ€“Ti shape memory alloys to assess their prospective use for seismic applications to be exploited as seismic resistant design and retrofit. In addition,Â the correlation of hysteretic behavior of Ni-Ti alloy in terms of cyclic loading number and history, mechanical properties at ambient temperature, equivalent damping, energy dissipation andÂ recovery stress were evaluated. The NiTi barÂ used is with weight percentage ofÂ Ti-43.98 at. % Ni 56.02 and diameter of 12 mm. The tensile cyclic test obtained demonstrated a rounded loading curve based on a 0.2 % offset. The as received bar exhibited superior pseudo-elastic behaviour and recentering through repeated cycling without significant degradation or permanent deformation but low energy dissipation due to narrow hysteresis while the steel rebar showed vice versa. Experimental results show potential for the use of SMAs in seismic applications and provide areas for continued research. It was concluded that the as-received pseudo elastic Ni-Ti bar is suitable for use in seismic mitigation despite of their ability to undergo cyclical strains at 6 % which is greater than 5 %, with minimal residual strain of 0.15% which is less than 1%.Â Â Â Â